Perspectives of pharmaceutical stakeholders on determinants of medicines accessibility at the primary care level - Hoda Ibrahim Rizk; Monira Mahmoud Elkholy; Abeer Abdou Barakat; Raghda Mostafa Mostafa Elsayed; Shaimaa A. M. Abd El Fatah (SpringerOpen, 2021)
Abstract Background Equitable access to essential medicines of maintained efficacy, safety, quality, and cost-effectiveness must be ensured by a well-functioning health system. This study aims to identify the determinants of patients' access to medicines at the primary health care (PHC) level from the perspectives of various (internal and external) stakeholders of the pharmaceutical system. Methods The study employed both quantitative and qualitative components. Quantitative component applied a descriptive a cross-sectional design and qualitative component applied an in-depth interview design. It was a health system research conducted at two (PHC) facilities (one urban and the other rural) in Egypt. It inquired upon political, economic, and managerial aspects of the pharmaceutical system utilizing the "Health System Assessment Approach: a How-To Manual" and the "WHO operational package for assessing, monitoring and evaluating country pharmaceutical situations." Results Analysis of the quantitative data extracted from the cross-sectional component with external stakeholders (patients) revealed that about one-third of patients in both facilities were unable to pay for the medicine. Patients in both settings took less than an hour to reach the PHC facility. The Percent of patients who believe that the private pharmacies' medicine is better than the PHC one was significantly higher in rural than urban group (24% and 10% respectively) and the percent of medicines dispensed was 50% and 66.7% in rural and urban groups respectively. Analysis of the qualitative data extracted from in-depth interviews with internal stakeholders (key informants from regulatory agencies, pharmaceutical industry, academia, pharmacists, and physicians) were summarized utilizing Strengths-Weaknesses-Opportunities-Challenges (SWOC) analysis approach. Various viewpoints toward the determinants of patients' access to medicines were disclosed. Conclusions The Percent of medicines dispensed was insufficient in both rural and urban facilities. There is a need to invest in building trust in generic medicine quality in the government health facilities focusing on improving medicine availability and ensuring enough amounts of high-quality drugs. Although there are drug committees in the two studied PHC facilities for demonstrating the prescribing and dispensing policies, yet the system required to enforce these policies is still deficient.